2021
DOI: 10.1108/edi-03-2021-0071
|View full text |Cite
|
Sign up to set email alerts
|

Four ways forward in studying sex-based harassment

Abstract: PurposeThe purpose of this paper is to identify promising themes of the papers in the special issues of Equality, Diversity and Inclusion dedicated to advancing scholarship on sex-based harassment.Design/methodology/approachA conceptual overview of the research pertaining to these themes and an analysis of the special issues papers' contributions to these themes.FindingsFour themes that represent important but relatively neglected lines of inquiry into sex-based harassment are identified. These are (1) the psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…As the findings of the policy analysis and survey illustrate, workplace training should consider the importance of macro-level socio-cultural influences (McCarthy & Moon, 2018) since the rationale is strong for anti-sexual harassment policies while still not producing successful outcomes. Few people openly support sexual harassment; yet the policies displayed cultural attitudes that lead to paying lip service to the abhorrence of sexual harassment while avoiding necessary steps to eliminating it, which may disrupt current organizational and societal patriarchal power structures (Berdahl & Bhattacharyya, 2021;Fraser, 2015;Johnson & Johnson, 2017;Sadler et al, 2018;Tinkler & Zhao, 2020). We agree with Popovich and Warren (2010) that workplace sexual harassment is a symptom of power abuse within organizations that needs to be addressed before sexual harassment can be eliminated.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As the findings of the policy analysis and survey illustrate, workplace training should consider the importance of macro-level socio-cultural influences (McCarthy & Moon, 2018) since the rationale is strong for anti-sexual harassment policies while still not producing successful outcomes. Few people openly support sexual harassment; yet the policies displayed cultural attitudes that lead to paying lip service to the abhorrence of sexual harassment while avoiding necessary steps to eliminating it, which may disrupt current organizational and societal patriarchal power structures (Berdahl & Bhattacharyya, 2021;Fraser, 2015;Johnson & Johnson, 2017;Sadler et al, 2018;Tinkler & Zhao, 2020). We agree with Popovich and Warren (2010) that workplace sexual harassment is a symptom of power abuse within organizations that needs to be addressed before sexual harassment can be eliminated.…”
Section: Discussionmentioning
confidence: 92%
“…Despite data collected over the past decade showing sexual harassment is a problem in Sub-Saharan African newsrooms (International Women's Media Foundation, 2013;authors), news organizations aren't implementing effective policies that ensure zero-tolerance work environments. Moreover, the gender essentialism underpinning various gender inequalities like sexual harassment (Berdahl & Bhattacharyya, 2021) carry over into anti-sexual harassment policymaking, which results in protecting the organization and perpetrators rather than the victims of sexual harassment. Not surprisingly, news organizations with policies have little impact on the level of experienced sexual harassment or the likelihood of reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual harassment—sometimes referred to as sex-based or gender-based harassment because it is rarely sexually motivated 12 14 —and sexual assault are widely documented, as are the negative consequences on victims’ well-being and careers 15 , 16 . Research has also identified negative repercussions for the workplace as a whole, such as studies linking masculinity contest cultures (i.e., work environments that reward strength, overconfidence, and competitiveness) to lower psychological safety 17 and organizational performance 18 .…”
Section: Introductionmentioning
confidence: 99%